Case Report: Tislelizumab-induced insulin-dependent diabetes mellitus: a case report and literature review - Ji, Panpan; Zhang, Yahui; Zhang, Wen; Leng, Bing; Nie, Ruifang; Shen, Chengwu; Yu, Hengcai (Frontiers in Pharmacology, 2025)
Tislelizumab is approved for cancer immunotherapy. Tislelizumab-induced insulin-dependent diabetes mellitus (IDDM) is infrequent, but life-threatening; to date, no reports have been published in English. The study aims to analyze the adverse effect. A case of tislelizumab-induced IDDM was reported. The study also reviewed published cases of developing IDDM after using tislelizumab, by systematic search of PubMed, CNKI, WANFANG and VIP (the latter three, Chinese article databases). Seventeen patients (including ours) were included. The mean age was 65.7 years and 73% (11/15) were male. IDDM usually appeared after 8.4 cycles. The mean random glycemia was 35.9 mmol/L, however, the hemoglobin A1c was only 8.5%. Eighty percent (12/15) presented with diabetic ketoacidosis (DKA). One hundred percent showed inappropriately low C-peptide (15/15) and undetectable autoantibodies (14/14). Insulin was immediately administered to all patients and 50% (8/16) had relatively stable glycemic control lastly. Similar to previous reports, tislelizumab-induced IDDM is characterized by a more rapid progression to severe insulin deficiency, frequently with DKA. However, unlike previous ones, islet autoantibodies were absent in all cases, possibly because of racial differences. These findings offer valuable safety warnings and allow doctors to identify and treat tislelizumab-induced IDDM timely.